LncRNAs Participate in Post-Resuscitation Myocardial Dysfunction Through the PI3K/Akt Signaling Pathway in a Rat Model of Cardiac Arrest and Cardiopulmonary Resuscitation - Hou, Jingying; Zeng, Chaotao; Zheng, Guanghui; Liang, Lian; Jiang, Longyuan; Yang, Zhengfei (Frontiers in Physiology, 2021)
In this study, we aimed to explore the role of lncRNAs in post-resuscitation myocardial dysfunction in a rat model of CA-CPR. A rat model of CA-CPR was constructed using a VF method. Myocardial functions, including cardiac output (CO), ejection fraction (EF), and myocardial performance index (MPI), were evaluated at the baseline, and 1, 2, 3, 4, and 6 h after resuscitation. A high throughput sequencing method was used to screen the differentially expressed lncRNAs, miRNAs, and mRNAs, which were further analyzed with bioinformatics. In addition, relationships between the molecules involved in the PI3K/Akt signaling pathway were explored with ceRNA network. Compared with the sham group, EF was significantly reduced and MPI was increased at the five consecutive time points in the CA-CPR group. 68 lncRNAs were upregulated and 40 lncRNAs were downregulated in the CA-CPR group, while 30 miRNAs were downregulated and 19 miRNAs were upregulated. Moreover, mRNAs were also differentially expressed, with 676 upregulated and 588 downregulated. GO analysis suggested that genes associated with cell proliferation, cell death and programmed cell death were significantly enriched. KEGG analysis showed that the PI3K/Akt, MAPK and Ras signaling pathways were the three most-enriched pathways. Construction of a ceRNA regulatory network indicated that LOC102549506, LOC103689920, and LOC103690137 might play important roles in the regulation of the PI3K/Akt signaling pathway in the CA-CPR treated rat. Taken together, LncRNAs, including LOC102549506, LOC103689920 and LOC103690137, might participate in post-resuscitation myocardial dysfunction by functioning as ceRNAs and regulating the PI3K/Akt signaling pathway.